Representasi Kepercayaan Diri Wanita Muslimah pada Iklan Sampo Wardah “The Real Hijab Expert” - Pitaloka, Desta Arum; Pudrianisa, Sheila Lestari Giza (Program Studi Ilmu Komunikasi UII, 2023)
This research examines the representation of Muslim women's self-confidence in Wardah shampoo advertisements in The Real Hijab Expert edition. The research uses a constructivist paradigm with the semiotic method of Charles Sanders Peirce, known for his triangle theory of meaning consisting of sign, object and interpretant. The results of this research show that the representation of Muslim women's self-confidence is shown dominantly in the Wardah advertisement for The Real Hijab Expert edition through signs in the form of movements, facial expressions, voice over, and typography which are included as indications of self-confidence. There are four indications of self-confidence according to Lauster, all of which are found in advertisements, namely believing in one's own abilities, acting independently in making decisions, having a positive self-concept, and daring to express opinions. By showing confident Muslim women, through the Wardah shampoo advertisement in The Real Hijab Expert edition, Wardah wants to convince Muslim women consumers that self-confidence can be formed through the use of Wardah shampoo.